Pajak ataukah Zakat Yang Lebih Besar Terhadap Konsumsi Masyarakat - Dwi Hastuti Lestari Komarlina; Andi Rustandi; Nanang Rusliana (Jurnal Ekonomi-Qu, 2020)
Indonesia is mostly Muslim, so the thought that in addition to taxation is possible zakat can also be a macro effect on people's consumption. The purpose of this research is to analyze: (1) the effect of tax and zakat on public consumption; (2) Taxes or zakat that have a better impact on people's consumption ability. The research method uses descriptive data series method to analyze the consumption patterns of people affected by ready-to-use income through tax and zakat estimates. Some analytical tools are correlation coefficient, determination coefficient, F-statistical testing, regression coefficient, trend, and effectiveness ratio. Obtained results: (1) Tax and zakat each have a significant and significant effect on public consumption through disposible income; (2) Tax margins are only slightly greater than marginal zakat, so that the relative tax impact is still more dominant in improving welfare as seen from its impact on the consumption capacity of the Indonesian people. The research implications make the thought and development of zakat a potential income to increase consumption and welfare of the Indonesian people.